Temporal trends in overweight and obesity and chronic dease risks among adolescents and young adults: A ten-year review at a tertiary institution in Nigeria (2023)
There is an increasing prevalence of obesity among college/university students in low- and middle-income countries, similar to the trend observed in high-income countries. This study aimed to describe the trend and burden of overweight/obesity and emerging associated chronic disease risks among students at the University of Ibadan (UI), Nigeria. This is a ten-year retrospective review of medical records of students (undergraduate and post-graduate) admitted between 2009 and 2018 at UI. Records of 60,168 participants were analysed. The Body Mass Index (BMI) categories were determined according to WHO standard definitions, and blood pressure was classified according to the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC7). The mean age of the participants was 24.8, SD 8.4 years. The majority were ≤ 40 years (95.1%). There was a slight male preponderance (51.5%) with a male-to-female ratio of 1.1:1; undergraduate students constituted 51.9%. The prevalence of underweight, overweight, and obesity were 10.5%, 18.7% and 7.2%, respectively. We found a significant association between overweight/obesity and older age, being female and undergoing postgraduate study (p = 0.001). Furthermore, females had a higher burden of coexisting abnormal BMI characterised by underweight (11.7%), overweight (20.2%) and obese (10.4%). Hypertension was the most prevalent obesity-associated non-communicable disease in the study population, with a prevalence of 8.1%. Also, a third of the study population (35.1%) had prehypertension. Hypertension was significantly associated with older age, male sex, overweight/obesity and family history of hypertension (p = 0.001). This study identified a higher prevalence of overweight and obesity than underweight among the participants, a double burden of malnutrition and the emergence of non-communicable disease risks with potential lifelong implications on their health and the healthcare system. To address these issues, cost-effective interventions are urgently needed at secondary and tertiary-level educational institutions.